Analysis of factor affecting financing with Islamic banks in agriculture sectors - Heri Sudarsono; Mustika Noor Mifrahi; Indah Susantun; Ari Rudatin; Sarastri Mumpumi Ruchba (Faculty of Business & Economics, Universitas Islam Indonesia, 2019)
Purpose: This study aims to determine the effect of non-performing finance, inflation, interest rates, Bank Indonesia Sharia Certificate variable, deposit and Industrial Production Index on the financing of the agricultural sector in Islamic banks.Methodology:This study uses analysis tools with the Vector Auto Regression (VAR) method. The VAR method is applied if the data used is stationary and there is no cointegration. If the data used is stationary but there is cointegration, the analytical tool that will be applied is the Vector Correction Model (VECM) method.Findings: There is causality between interest rates and financing in the agricultural sector. This situation can be interpreted that any increase in interest rates will result in people preferring financing to Islamic banks. Profit sharing and margins do not directly influence the increase in interest rates in conventional banks so that the increase in interest rates is relatively a cheaper cost of financing. Conversely, if there is a decrease in the interest rate on conventional banks, it will make people more likely to choose financing in conventional banks rather than in Islamic banks Originality:This study enrich the discussion in factors affecting financing with Islamic Banks in agriculture sectors.